Consensus recommendation for meningococcal disease prevention in children and adolescents in the Middle East region - Atef Shibl; Haysam Tufenkeji; Mohamed Khalil; Ziad Memish (Springer, 2019)
Facing the availability of the new generation of quadrivalent meningococcal conjugate vaccines (Menveo®, Menactra® and others pending for license) and their recent implementation in Saudi Arabia, experts from 11 countries of the Middle East region met at a "Meningococcal Leadership Forum" (MLF), which took place in May 2010 in Dubai. The participants of the conference discussed the importance of introducing the concept of conjugate vaccines - especially for children and adolescents - and elaborated a consensus recommendation to support healthcare professionals and decision makers with their expertise. In experts' opinion, conjugate vaccines are the best choice for the prevention of meningococcal disease caused by serogroups A, C, W-135 and Y. As quadrivalent meningococcal conjugate vaccines are registered and available in the Middle East region, they should replace plain polysaccharide vaccines and be integrated in pediatric and adolescent vaccination schedules, including infant vaccination concomitantly with basic EPI vaccines when licensed.